Upper bound for broadband radiofrequency field disruption of magnetic compass orientation in night-migratory songbirds - Leberecht, B; Wong, SY; Satish, B; Döge, S; Hindman, J; Venkatraman, L; Apte, S; Haase, K; Musielak, I; Dautaj, G; Solov'yov, IA; Winklhofer, M; et al. (National Academy of Sciences, 2023)
Night-migratory songbirds have a light-dependent magnetic compass sense, the mechanism of which is thought to depend on the photochemical formation of radical pairs in cryptochrome (Cry) proteins located in the retina. The finding that weak radiofrequency (RF) electromagnetic fields can prevent birds from orienting in the Earth’s magnetic field has been regarded as a diagnostic test for this mechanism and as a potential source of information on the identities of the radicals. The maximum frequency that could cause such disorientation has been predicted to lie between 120 and 220 MHz for a flavin–tryptophan radical pair in Cry. Here we show that the magnetic orientation capabilities of Eurasian blackcaps (Sylvia atricapilla) are not affected by RF noise in the frequency bands 140 to 150 MHz and 235 to 245 MHz. From a consideration of its internal magnetic interactions, we argue that RF field effects on a flavin-containing radical-pair sensor should be approximately independent of frequency up to 116 MHz and that birds’ sensitivity to RF disorientation should fall by about two orders of magnitude when the frequency exceeds 116 MHz. Taken together with our earlier finding that 75 to 85 MHz RF fields disrupt the magnetic orientation of blackcaps, these results provide compelling evidence that the magnetic compass of migratory birds operates by a radical pair mechanism.